Risk factors and complications associated with intra-operative or post-operative identification of a PFO in cardiac surgery patients: A cohort study - Laghlam, Driss; Coroyer, Lucas; Martial, Paul-Jun; Estagnasie, Philippe; Squara, Pierre; Nguyen, Lee S. (Frontiers in Neurology, 2023)
Introduction It is unknown whether patent foramen ovale (PFO) reopening in the peri-operative setting of cardiac surgery affects the risk for stroke and post-operative outcomes. Methods We performed a single-center, retrospective study based on a prospectively collected database in a tertiary cardiac surgery center. Using logistic regression, we assessed risk factors of PFO finding around surgery and subsequent clinical complications. Results Between January 2007 and July 2019, 11034 patients who underwent cardiac surgery in our center were included. A total of 233 patients (2.1%) presented a finding of PFO including 138 per-operative disclosures and 95 post-operative finding for hypoxemia. In the whole cohort, the mean age was 68.4 ± 11.5 years including 73.9% of men. Post-operative PFO finding was associated with more ischemic strokes compared with per-operative finding and control group [7(7.4%) vs. 3(2.2%) vs. 236(2.2), respectively; p = 0.003]. Moreover, patients with post-operative PFO reopening experienced a higher rate of pneumonia, reintubation, and longer length of stay in the ICU. Post-operative reopening of PFO, but not per-operative finding, was independently associated with ischemic strokes {adjusted odds-ratio = 3.5, 95% confidence interval (CI) [1.6–7.8]; p = 0.002}. Other variables associated with stroke incidence included age, mitral valve surgery, and ascending aorta surgery. Per- or post-operative PFO closure was associated with reduced adverse respiratory outcomes and a trend of the lower cerebral ischemic event. Conclusion Patent foramen ovale finding incidence in peri-operative cardiac surgery care was rare (2%) but post-operative finding of PFO was associated with a increased risk of ischemic strokes, worsened respiratory outcomes, and prolonged hospitalization.